Development of medium- and low-density fibreboards made of coconut husk and bound with tannin-based adhesives. (1st October 2016) - Fitzken Da Vinci M. Niro, John; Kyriazopoulos, M.; Bianchi, S.; Mayer, I.; Eusebio, D. A.; Arboleda, J. R.; Lanuzo, M. M.; Pichelin, F.
Abstract : Fibreboards made of coconut husk and bonded with tannin-based adhesives could represent an affordable building material in the Philippine for the low-income population. Coconut husk is a large available and not full-exploited byproduct of the coconut industry, and suitable tannins could be extracted from the bark of local tree species. Medium-density boards (700–800 kg m −3 ) were produced at the lab-scale and the influence of pressing cycle parameters, material preconditioning, and tannin adhesive formulation investigated and correlated to the chemical characteristics of the husk. Mimosa tannin adhesives with and without hardener (hexamine) and at different pH were considered. The produced board satisfied the mechanical requirements for the Japanese standard JIS A 5905 (Type 15) and showed also remarkably low-volatile emissions. An initial moisture content of the husk between 9 and 15% was necessary for an efficient adsorption of the adhesive. The presence of silica on the fibre surface enhanced the auto-condensation of tannin molecule reducing the need of hardener in the adhesive formulation. Low-density boards (250–300 kg m −3 ) were also produced. Their thermal conductivity (0.071–0.082 W m −2 K −1 ) satisfied the requirement for JIS A 5905 Class A insulation boards.